Undetected hypothyroidism: A rare dental diagnosis - Dudhia, Sonal B (Medknow Publications & Media Pvt Ltd, 2014)
Thyroid dysfunction is the second most common glandular disorder of the endocrine system, which may rear its head in any system in the body including the mouth. The oral cavity is adversely affected by either an excess or deficiency of thyroid hormone. Childhood hypothyroidism known as cretinism is characterized by thick lips, large protruding tongue (macroglossia), malocclusion and delayed eruption of teeth. Neonatal screening for congenital hypothyroidism is not performed in all countries and not every affected patient might be determined by neonatal screening alone. The dentist by detecting the early signs and symptoms of hypothyroidism can refer the patient for medical diagnosis and treatment and avoid potential complications of treating patients with uncontrolled disease. Herein, we present a case of undetected hypothyroidism in a 13-year-old female patient based on dental features by oral medicine specialists.